DARWIN EU® is an electronic platform for the collection and analysis of health data in the European Union - K. S. Radaeva; E. V. Verbitskaya (Реальная клиническая практика: данные и доказательства)
The growing volume and complexity of data that is currently being collected in a variety of settings and devices is of varying degrees and quality, posing a challenge for the public health sector to develop a robust electronic system that can be collected, analyzed and made available to clinicians. The creation of a system, the development of the capabilities and potential of information technologies for obtaining, managing and analyzing a large amount of data, will allow to identify facts regarding the safety and effectiveness of the use of drugs, to investigate the validity of statements made by pharmaceutical companies, to obtain a more accurate characterization of treatment methods in individual healthcare sectors and to provide doctors with quick and constant access to this information, which will facilitate its use in the treatment of patients. The development of such a tool is a priority for the health care system in a changing world. An example of such a tool is the Data Analysis and Real Word Interrogation Network (DARWIN EU®), which was launched on February 9, 2022 by the European Medicines Agency. The purpose of this article is to review the history of creation, organizational structure, operating principles, current experience of the European Union regulatory network and comparison with the experience of international regulatory bodies. The article, along with the experience of the European Medicines Agency, also considers similar initiatives in the US and Canada.